Cervical cancer prevention in Senegal: an International Cooperation Project Report - Gabrielli, Simona; Maggioni, Elena; Fieschi, Laura (Acta Biomedica Atenei Parmensis, 2018)
Background: Cervical cancer is the second most common women’s cancer in less developed regions and it is the leading cause of cancer mortality among women in Senegal. Because of the high costs, cervical cancer prevention is very rare in developing countries and it is often based on visual inspection methods. The University of Parma (CUCI) and the MANI association have developed a cervical cancer screening project addressed to rural Senegal communities. The aim of the project was to disseminate the cytocervical sampling technique among Senegalese nurses and midwives, as a completion to the local visual inspection method. Other objectives were to verify the prevalence of precancerous lesions and to evaluate cervical cancer knowledge and attitudes among women who participated at the screening campaign. Interventions: A theoretical and practical training plan on cervical cancer screening was provided to the local health workers at various levels. The screening was performed through a first step visual inspection exam to 203 women, followed by a Pap smear in case of positive outcome. 20 women participated also to a structured interview. Results: The Pap smear material was adequate in all the samples collected where this indicates that the objective to disseminate cervical cancer screening techniques has been achieved. Of the 203 women involved in the screening project, 68 were tested positive at the first step and 38 of them were submitted to Pap tests. Conclusion: The difficulties encountered confirm how Pap tests have overall proved inordinately complex and expensive for developing countries. It seems more sensible to deal first with global health in terms of basic hygienic sanitation, including an educational component in screening programs in order to sensitize women to the risk factors of cervical cancer.